Dissecting the role of epidermal growth factor receptor catalytic activity during liver regeneration and hepatocarcinogenesis. Issue 2 (10th October 2015) - López‐Luque, Judit; Caballero‐Díaz, Daniel; Martinez‐Palacián, Adoración; Roncero, César; Moreno‐Càceres, Joaquim; García‐Bravo, María; Grueso, Esther; Fernández, Almudena; Crosas‐Molist, Eva; García‐Álvaro, María; Addante, Annalisa; Bertran, Esther; et al.
Abstract : Different data support a role for the epidermal growth factor receptor (EGFR) pathway during liver regeneration and hepatocarcinogenesis. However, important issues, such as the precise mechanisms mediating its actions and the unique versus redundant functions, have not been fully defined. Here, we present a novel transgenic mouse model expressing a hepatocyte‐specific truncated form of human EGFR, which acts as negative dominant mutant (ΔEGFR) and allows definition of its tyrosine kinase–dependent functions. Results indicate a critical role for EGFR catalytic activity during the early stages of liver regeneration. Thus, after two‐thirds partial hepatectomy, ΔEGFR livers displayed lower and delayed proliferation and lower activation of proliferative signals, which correlated with overactivation of the transforming growth factor‐β pathway. Altered regenerative response was associated with amplification of cytostatic effects of transforming growth factor‐β through induction of cell cycle negative regulators. Interestingly, lipid synthesis was severely inhibited in ΔEGFR livers after partial hepatectomy, revealing a new function for EGFR kinase activity as a lipid metabolism regulator in regenerating hepatocytes. In spite of these profound alterations, ΔEGFR livers were able to recover liver mass by overactivating compensatory signals, such as c‐Met. Our results also indicate that EGFR catalytic activity is critical in the early preneoplastic stages of the liver because ΔEGFR mice showed a delay in the appearance of diethyl‐nitrosamine‐induced tumors, which correlated with decreased proliferation and delay in the diethyl‐nitrosamine‐induced inflammatory process. Conclusion : These studies demonstrate that EGFR catalytic activity is critical during the initial phases of both liver regeneration and carcinogenesis and provide key mechanistic insights into how this kinase acts to regulate liver pathophysiology. (Hepatology 2016;63:604–619)